2022
DOI: 10.1007/978-3-030-76000-7_8
|View full text |Cite
|
Sign up to set email alerts
|

How Reliance on Allomaternal Care Shapes Primate Development with Special Reference to the Genus Homo

Abstract: According to the Cooperative Breeding Hypothesis, slow-maturing apes with the life history attributes of those in the line leading to the genus Homo could not have evolved unless male and female allomothers had begun to help mothers care for and provision offspring. The unusual way hominins reared their young generated novel phenotypes subsequently subjected to Darwinian social selection favoring those young apes best at monitoring the intentions, mental states, and preferences of others and most motivated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 128 publications
1
14
0
Order By: Relevance
“…Prior to the present experimental study, anthropological and evolutionary theory had suggested that grandparents influence child development (Hawkes, 2020;Hrdy & Burkart, 2022), but empirical analyses of archival caregiver reports found no effect on early prosociality (Sadruddin et al, 2019). Yet, cognizant of the value that Latinx culture places on grandparenting (Goodman & Silverstein, 2002;Mendoza et al, 2018;Raphael, 1989) and of the emphasis on prosociality in the Latinx value system (Carlo & Conejo, 2019;Carlo et al, 2022;Ramírez-Esparza et al, 2012, we conducted a study in lowincome, urban neighborhoods that were almost entirely Latinx and found the hypothesized association between grandparents and early childhood prosociality.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Prior to the present experimental study, anthropological and evolutionary theory had suggested that grandparents influence child development (Hawkes, 2020;Hrdy & Burkart, 2022), but empirical analyses of archival caregiver reports found no effect on early prosociality (Sadruddin et al, 2019). Yet, cognizant of the value that Latinx culture places on grandparenting (Goodman & Silverstein, 2002;Mendoza et al, 2018;Raphael, 1989) and of the emphasis on prosociality in the Latinx value system (Carlo & Conejo, 2019;Carlo et al, 2022;Ramírez-Esparza et al, 2012, we conducted a study in lowincome, urban neighborhoods that were almost entirely Latinx and found the hypothesized association between grandparents and early childhood prosociality.…”
Section: Discussionmentioning
confidence: 75%
“…If previous empirical work has not identified the role of grandparents in the development of grandchild prosociality, why would this be different in the case of Latinx families? Fitting in with theories of prosociality in Latinx families (Carlo & Conejo, 2019;Rogoff & Mejía-Arauz, 2022), theories in cultural anthropology and evolutionary biology have suggested that living conditions that include extended family members may enhance early sociocognitive, emotional, and physical development (Hawkes, 2020;Hawkes et al, 1997;Hrdy, 2009;Hrdy & Burkart, 2022).…”
Section: Grandparents Grandchildren and Latinx Culturementioning
confidence: 99%
“…Human infants are born into large social networks and face the challenge of learning about them. Over their first year, infants' social skills expand (Tomasello, 2016), as does the number of people they interact with (Helfrecht et al, 2020;Hrdy & Burkart, 2022). Thus, with minimal language to guide them, infants face a particular challenge when learning about their social worlds: they must rely in part on observations to learn about the dispositions and relationships of the people around them.…”
Section: Introductionmentioning
confidence: 99%
“…We argue instead that heightened fearfulness is better viewed as part of a suite of evolved features that serve to signal, in a reflex-like way, adults' caregiving motivations and actions toward helpless babies, increasing the chances that infants will be attended to, cared for, form attachments, and survive. Other infantile adaptations that foster infant attention and attachment, including neotenous facial features (Lorenz's kindchenschema, or baby schema), smiles, laughs, and vocal behaviors such as coos and cries (e.g., Bründl et al, 2021;Hrdy & Burkart, 2022), decline in influence with time. In contrast, Grossmann's view of humans' heightened fearfulness is best conceptualized as a deferred adaptation (an evolutionary solution to a problem beginning early in life and serving the same or similar function later in development, Hernández Blasi & Bjorklund, 2003), having both an immediate function in infancy (increasing the chances of adult caregiving) and a deferred one later in life (contributing to older humans' enhanced ability to cooperate, including in childcare).…”
Section: Introductionmentioning
confidence: 99%